Clinical-epidemiological characterization of adult women diagnosed with COVID-19 in a hospital in northern Peru (Journal of Pharmaceutical Negative Results, 2022)
Objective: to describe the clinical-epidemiological characteristics of adult women with COVID-19 diagnosis in an EsSalud Cajamarca Hospital during 2020 - 2021. Method: the methodology is descriptive, retrospective, observational and cross-sectional. The population consisted of adult women, and the sample consisted of 216 women. A data collection form was applied to the NOTI COVID registry and the clinical history was used. Results: Of the 216 confirmed cases, 67.6% of the cases were women between 30 and 49 years of age. Ninety-seven percent were from the department of Cajamarca. Of these, 11.2% were pregnant women, 58.3% of whom were in the third trimester of pregnancy. More than half (81.1%) had a positive serologic test result, and 50.9% were IgG. Of the COVID-19 women, 41.7% had contact with a positive case and only 0.9% had contact with a suspected COVID-19 case. The most frequent comorbidities were arterial hypertension (21.2%), diabetes (15.4%) and obesity (13.5%). The degree of severity was mostly mild (57.9%), they presented general malaise (14.3%), and cough (13.3%). 63.5% presented interstitial ground-glass pattern and 34.9% presented hypertransaminasemia and 27.9% lymphopenia. Conclusions: adult women with a COVID-19 diagnosis had comorbidities such as hypertension, diabetes and obesity.